Doa dan Penyembuhan Ilahi: Studi Teks Yakobus 5: 14-16 - Ana Ariesanita; Lenny; Yanto Paulus Hermanto (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
Illnesses are life problems that believers often face. Various ways are used to get physical healing, apart from medication, and spiritually by praying to God for healing. Prayers are carried out privately or with prayer support from church ministers. However, a disease that never heals often leads to despair and loss of hope. There may even be disappointment with God because the prayer request for healing was not granted. This research uses a text analysis study approach of James 5:14-16 to understand the correlation of prayer and the divine aura for believers. James explains that heavenly appearances include both spiritual and physical aspects. This text explains that the prayer request of faith relates to the forgiveness of sins, which impacts divine healing from sickness due to sins that entangle believers. So in his letter, James emphasizes rapprochement with God so that the prayers offered to Him are not hindered. With the correct understanding of this Bible text, believers can pray effectively to experience divine healing and restoration of their lives.